STRATEGI KOMUNIKASI PROTOKOLER DALAM MENYIKAPI PERUBAHAN AGENDA PIMPINAN DAERAH PADA BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIS DAERAH - Subang, Donatus Bernald; Mustafa, Intan; Retu, Markus Kristian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Changes in the schedule of regional leaders are an inevitable part of the dynamic nature of local government administration. This condition requires the Protocol and Leadership Communication Division to implement effective, adaptive, and well-coordinated communication strategies to ensure that protocol duties are carried out optimally. This study aims to analyze protocol communication strategies in responding to changes in regional leaders’ agendas, identify the obstacles encountered, and examine the efforts undertaken to overcome these challenges. This research employs a qualitative approach using a case study design and was conducted at the Protocol and Leadership Communication Division of the Regional Secretariat of Sikka Regency. Data were collected through in-depth interviews, observation, and documentation, with informants selected using purposive sampling. Data analysis was carried out using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that protocol communication strategies in addressing changes in regional leaders’ agendas are implemented through strengthened internal coordination, intensive vertical communication with regional leaders, and ethical and professional external communication with relevant stakeholders. The main obstacles identified include time constraints, differences in perceptions among related parties, and limitations in human resources. To address these challenges, efforts are made to enhance communication intensity, conduct routine evaluations, clarify task distribution, and improve the competence of protocol officers. This study concludes that adaptive and well-coordinated protocol communication strategies play a crucial role in ensuring the smooth implementation of regional leaders’ agendas amid dynamic changes. ABSTRAK Perubahan agenda pimpinan daerah merupakan fenomena yang tidak terpisahkan dari dinamika penyelenggaraan pemerintahan daerah. Kondisi tersebut menuntut Bagian Protokol dan Komunikasi Pimpinan untuk memiliki strategi komunikasi yang efektif, adaptif, dan terkoordinasi agar pelaksanaan tugas keprotokolan tetap berjalan optimal. Penelitian ini bertujuan untuk menganalisis strategi komunikasi protokoler dalam menyikapi perubahan agenda pimpinan daerah, mengidentifikasi hambatan yang dihadapi, serta upaya yang dilakukan untuk mengatasinya. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus, yang dilaksanakan di Bagian Protokol dan Komunikasi Pimpinan Sekretariat Daerah Kabupaten Sikka. Teknik pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan dokumentasi, dengan informan yang dipilih secara purposive. Analisis data dilakukan menggunakan model interaktif Miles dan Huberman yang meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi komunikasi protokoler dalam menyikapi perubahan agenda pimpinan daerah dilakukan melalui penguatan koordinasi internal, komunikasi vertikal yang intensif dengan pimpinan daerah, serta komunikasi eksternal yang beretika dan profesional dengan para pemangku kepentingan. Hambatan utama yang dihadapi meliputi keterbatasan waktu, perbedaan persepsi antar pihak terkait, serta keterbatasan sumber daya manusia. Untuk mengatasi hambatan tersebut, dilakukan upaya peningkatan intensitas komunikasi, evaluasi rutin, pembagian tugas yang jelas, serta peningkatan kompetensi aparatur protokoler. Penelitian ini menyimpulkan bahwa strategi komunikasi protokoler yang adaptif dan terkoordinasi memiliki peran penting dalam menjaga kelancaran pelaksanaan ag enda pimpinan daerah di tengah perubahan yang dinamis.